Oyster extracts attenuate pathological changes in non-alcoholic steatohepatitis (NASH) mouse model. (January 2016) - Watanabe, Mitsugu; Fuda, Hirotoshi; Okabe, Hiroaki; Joko, Sae; Miura, Yusuke; Hui, Shu-Ping; Yimin,; Hamaoka, Naohiro; Miki, Emiko; Chiba, Hitoshi
Highlights: Phenolic compound, DHMBA. is a natural antioxidant isolated from the Pacific oyster. The aim is to investigate in vivo effect of DHMBA-rich oyster extracts (DOE). DOE attenuated obesity and insulin resistance in NASH model mouse. DOE also attenuated steatosis, inflammation, fibrosis, and apoptosis in liver. Abstract: The phenolic compound 3, 5-dihydroxy-4-methoxybenzyl alcohol (DHMBA) is a natural antioxidant recently isolated from the Pacific oyster. DHMBA, up to a concentration of 500 µM, has demonstrated a strong in vitro hepatocyte-protective effect from oxidative stress without any cytotoxicity. This study investigated the in vivo potential of DHMBA-rich oyster extracts (DOE) for prevention or attenuation of non-alcoholic steatohepatitis (NASH). NASH-model mice, developed by supplementation of a high-fat diet for 23 weeks and intravenous injections of oxidised low-density lipoproteins, exhibited obesity, insulin resistance, hepatic steatosis, inflammation, fibrosis, and apoptosis. These changes were significantly moderated by supplementation of DOE. The search for an underlying mechanism determined that DOE significantly improved the redox status of DNA, proteins, and lipids. Moreover, DOE suppressed the increase of hepatic expression of PPARγ and CD36 (fatty acid transporter) in the NASH-model mice. DOE might serve as a functional food for people at elevated risk for NASH .